Manipulating the Expression of Glycogen Phosphorylase in Synechococcus elongatus PCC 7942 to Mobilize Glycogen Storage for Sucrose Synthesis - Dan, Yu; Sun, Jiahui; Zhang, Shanshan; Wu, Yannan; Mao, Shaoming; Luan, Guodong; Lu, Xuefeng (Frontiers in Bioengineering and Biotechnology, 2022)
Cyanobacteria are promising photosynthetic chassis to produce biofuels, biochemicals, and pharmaceuticals at the expense of CO2 and light energy. Glycogen accumulation represents a universal carbon sink mechanism among cyanobacteria, storing excess carbon and energy from photosynthesis and may compete with product synthesis. Therefore, glycogen synthesis pathway is often targeted to increase cyanobacterial production of desired carbon-based products. However, these manipulations caused severe physiological and metabolic impairments and often failed to optimize the overall performances of photosynthetic production. Here in this work, we explored to mobilize the glycogen storage by strengthening glycogen degradation activities. In Synechococcus elongatus PCC 7942, we manipulated the abundances of glycogen phosphorylase (GlgP) with a theophylline dose-responsive riboswitch approach, which holds control over the cyanobacterial glycogen degradation process, and successfully regulated the glycogen contents in the recombinant strain. Taking sucrose synthesis as a model, we explored the effects of enhanced glycogen degradation on sucrose production and glycogen storage. It is confirmed that under non-hypersaline conditions, the overexpressed glgP facilitated effective mobilization of glycogen storage and resulted in increased secretory sucrose production. The findings in this work provided fresh insights into the area of cyanobacteria glycogen metabolism engineering, and would inspire the development of novel metabolic engineering approaches for efficient photosynthetic biosynthesis.